Penerapan Design Thinking dan SUS pada Pengembangan Website SIA SMA Sedes Sapientiae - Pinandhito, Azadirachta Priyo; Cahyono, Ariya Dwika (STMIK Banjarbaru, 2025)
User experience in web-based academic information systems is strongly influenced by the efficiency and intuitiveness of the user interface design. This study focuses on developing the user interface of the Academic Information System at SMA Sedes Sapientiae Jambu, which previously had not been fully optimized in presenting students’ academic progress reports. By applying the Design Thinking method, feature requirements were identified and designed according to users’ needs and preferences. To evaluate usability, the System Usability Scale (SUS) was employed after the system was developed. The evaluation results indicated a score in category “B” and a “good” rating on the adjective scale. These findings demonstrate that the Design Thinking approach contributes positively to enhancing usability and improving user comfort in accessing the academic information system.Keywords: User Interface; Design Thinking; System Usability Scale; Academic Information System, User Experience AbstrakPengalaman pengguna dalam sistem informasi akademik berbasis website dipengaruhi oleh desain antarmuka pengguna yang efisien dan intuitif. Penelitian ini menitikberatkan pada pengembangan tampilan pengguna Sistem Informasi Akademik (SIA) di SMA Sedes Sapientiae Jambu yang sebelumnya belum maksimal dalam menyajikan laporan perkembangan akademik siswa. Melalui penerapan metode Design Thinking, kebutuhan fitur diidentifikasi sekaligus dirancang sesuai dengan keinginan dan kebutuhan. Untuk menilai tingkat kegunaan, digunakan metode System Usability Scale (SUS) setelah sistem selesai dikembangkan. Hasil evaluasi menunjukkan nilai dengan kategori “B” serta penilaian “good” pada skala adjektiva. Temuan ini membuktikan bahwa pendekatan design thinking mampu memberikan kontribusi positif terhadap peningkatan kegunaan dan kenyamanan pengguna dalam mengakses SIA di SMA Sedes Sapientiae Jambu.